Optimizing Islamic Boarding School-Based Entrepreneurship Models in the Digital Economy Era: Challenges and Opportunities at the Jaddung Pragaan Sumenep Islamic Boarding School - Mohammad Khoirur Rachman; Ahmad Mohammad Tidjani (Penerbit Hellow Pustaka, 2024)
Islamic boarding schools, or pondok pesantren are traditional Islamic educational institutions that play a significant role in shaping the character and intellectual capacity of their students, or santri. In the modern era, Islamic boarding schools face both challenges and opportunities in fostering entrepreneurship, especially amidst digital disruption that is transforming business systems and models. This study examines how Islamic boarding schools, particularly in Sumenep Regency, can develop santri entrepreneurial independence by utilizing technology and innovative entrepreneurial approaches. Through a curriculum that integrates religious and general education, as well as practical skills training, pesantren strive to equip santri to face challenges in society. Empowering santri in the field of entrepreneurship is crucial in creating a generation that is not only strong in religious understanding but also equipped with relevant skills. This study finds that the success of entrepreneurial independence in Islamic boarding schools largely depends on smart strategies that involve leveraging available resources and collaborating with alumni. The results show that Islamic boarding schools can serve as agents of social change, advancing both education and the economy within the community.